2015
DOI: 10.1037/xge0000085
|View full text |Cite
|
Sign up to set email alerts
|

The snooze of lose: Rapid reaching reveals that losses are processed more slowly than gains.

Abstract: Decision making revolves around weighing potential gains and losses. Research in economic decision making has emphasized that humans exercise disproportionate caution when making explicit choices involving loss. By comparison, research in perceptual decision making has revealed a processing advantage for targets associated with potential gain, though the effects of loss have been explored less systematically. Here, we use a rapid reaching task to measure the relative sensitivity (Experiment 1) and the time cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 78 publications
(131 reference statements)
2
46
0
Order By: Relevance
“…Electrophysiologically, this finds echo with results showing that lateral intraparietal neurons initiate their firing more quickly in response to rewarding versus non-rewarding stimuli (Peck et al, 2009). The present findings may thus provide neurophysiological grounds for the behavioral evidence that decision-making unfolds more quickly in contexts where the best option is a net gain compared with when it is loss avoidance (Chapman et al, 2015). Additionally, these results may help explain recent evidence for mixed representations in the literature, in that the observed temporal shift in encoding may have been obscured using less temporally-resolved techniques such as fMRI.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Electrophysiologically, this finds echo with results showing that lateral intraparietal neurons initiate their firing more quickly in response to rewarding versus non-rewarding stimuli (Peck et al, 2009). The present findings may thus provide neurophysiological grounds for the behavioral evidence that decision-making unfolds more quickly in contexts where the best option is a net gain compared with when it is loss avoidance (Chapman et al, 2015). Additionally, these results may help explain recent evidence for mixed representations in the literature, in that the observed temporal shift in encoding may have been obscured using less temporally-resolved techniques such as fMRI.…”
Section: Discussionsupporting
confidence: 55%
“…An interesting possibility is that expected value and motivational salience may be expressed at different moments during movement preparation. Support for this comes from behavioral work by Chapman et al (2015), who demonstrated that when forced to respond rapidly (reaction times Յ425 ms), action selection is quicker when the best possible outcome entails obtaining a reward compared with evading a punishment. Importantly, however, this reward-related processing advantage disappeared when response initiation was delayed by 500 ms, suggesting that when there are no net positive options, it takes extra time for the brain to implement rational behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Chapman et al (2010a, b); Gallivan and Chapman (2014)]. Whereas this finding is certainly novel in the context of previous work that has used (or relied on) spatial averaging behavior to reveal the parallel encoding of competing movements [and/or probe the effects of distractors on reaching; see Buc Calderon et al (2015); Chapman et al (2015); Gallivan et al (2011);Meegan and Tipper (1998); Stewart et al (2014); Tipper et al (1997Tipper et al ( , 2000], the absence of spatial averaging effects here is perhaps to be expected, given that movements were initiated only after the target was cued.…”
Section: Tests For Cooptimization During the Early Reach Trajectorymentioning
confidence: 48%
“…Adapted from Ref. . (C) Response‐locked analysis of changes in primary motor cortex (M1) excitability to transcranial magnetic stimulation (TMS) pulses, measured via normalized motor evoked potentials (MEPs) toward chosen (red) versus unchosen (blue) options.…”
Section: Bringing Two Halves Together: Decision Making As a Continuoumentioning
confidence: 99%
“…80,81 Under these conditions, participants initially execute an averaged movement between both options before ultimately selecting one. Furthermore, it has been shown that the probability, 81 number, 80,82,83 spatial arrangement, 80,84 luminance, 85 reward-association, 86,87 and symbolic representation 88 of targets all impact rapid reach trajectories.…”
Section: Behaviormentioning
confidence: 99%